Відтворення рис національної мовної особистості як ознака ідіостилю Анатолія Дімарова - Кохан, Ю.І. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2005)
В статье анализируется фразеология произведений Анатолия Димарова как проявление ориентации автора на живую народную речь и отражение его стремления воспроизвести черты украинской национально-языковой личности. The article approaches A. Dymarov's phraseology as an example of his focus at the live people's vernacular and the reflection of his aspiration to reveal characteristic features of the Ukrainian national linguistic personality.
Keywords: Дімаров; ідіостиль; національна мовна особистість